Molybdenum carbide nanotubes: a novel multifunctional material for label-free electrochemical immunosensing. Issue 33 (9th August 2016) - Zhai, Qingfeng; Zhang, Xiaowei; Li, Jing; Wang, Erkang
Abstract : Herein, a multifunctional nanoarchitecture has been developed by integrating well-crystalline molybdenum carbide (Mo2 C) nanotubes and an electrochemical indicator – thionin (TH). Abstract : Herein, a multifunctional nanoarchitecture has been developed by integrating well-crystalline molybdenum carbide (Mo2 C) nanotubes and an electrochemical indicator – thionin (TH). The Mo2 C nanotubes were synthesized through the self-degradable template method and high-temperature calcination, and their structure and morphology were characterized through scanning electron microscopy (SEM), X-ray diffraction (XRD) and transmission electron microscopy (TEM). Due to the high electrocatalytic properties, excellent conductivity and highly active surface area of Mo2 C nanotubes, the Mo2 C-based material was used as a nanocarrier to load TH molecules for the development of a label-free electrochemical immunosensor for α-fetoprotein (AFP) detection. The decorated TH probe on the Mo2 C nanotubes not only acted as a bridging molecule to effectively capture and immobilize primary anti-AFP on the Mo2 C nanotubes, but also acted as a signal indicator for the detection of AFP. The proposed immunosensor exhibited excellent selectivity (with a detection limit of 3 pg mL −1 ), high stability and good reproducibility by combining the unique structure and features of the Mo2 C nanotubes. Furthermore, this sensing platform was finally used for the detection of AFP in human serum with satisfactory results. Therefore, the Mo2 C nanotubes can be considered as a candidate carbon material for fabrication of simple, label-free and ultrasensitive electrochemical sensors, broadening the application of this material.